Vintage crime: a short history of wine fraud - Gibb, Rebecca (University of California Press, 2023)
"The world of wine prides itself on its aura of respectability, but it has always had a murky side. Packed with engaging vignettes, Vintage Crime brings to life famous enthusiasts and crafty con artists from ancient Rome to modern-day California. It also introduces us to lesser-known industry figures: the scrupulous merchants, honest growers, and cutting-edge scientists who have led the fight against fraudsters. Author Rebecca Gibb holds the rare, sought-after distinction of Master of Wine, yet she writes in an engaging style that doesn't require any prior wine knowledge, skillfully synthesizing popular wine histories for amateur sleuths and armchair sommeliers alike. Vintage Crime will intrigue the most sated of wine drinkers with its juicy tales of deception, raising interesting questions along the way: what counts as wine, why do we drink it, and what makes a wine truly authentic?"--